Wiener filter applied with a multi-channel method for EBT2 film dosimetry. Issue 6 (1st August 2016) - Chang, Liyun; Du, Yi-Chun
Abstract : Purpose: – EBT2 film, a convenient quality assurance (QA) tool with high 2D dosimetry resolution, has been widely used in the dosimetry application of radiation therapy with lots of benefits especially its self-development, water equivalent, energy independent and high spatial resolution. However, the higher inhomogeneity between the pixels of EBT2 image, needed to be averaged out according to the traditional method, but it could sacrifice the spatial resolution. To solve this problem, the purpose of this paper is to introduce a Wiener filter (WF) technique applied with a multi-channel (MC) method. Design/methodology/approach: – The EBT2 film was calibrated by using the percentage depth dose method combined with the WF technique and a MC method. Then the calculated film doses were compared with the measurement doses by the edge detector with the water phantom. Findings: – With high spatial resolution to be 0.2 mm, the results demonstrate that the EBT2 film calibration through both of the WF technique and MC method has higher accuracy (within 2 percent) and lower uncertainty. Originality/value: – A new technique of WF with MC method was presented to calibrate the dosimetry system of EBT2 film. With high spatial resolution (0.2 mm), the studies show that the combination of WF technique with MC method can have high accuracy with low noises to calibrate EBT2 film. This method can also be applied to all the QAs of treatment planning of radiation therapy by using the EBT2 film.